Genetic Determinism in Community Staphylococcus and Methicillin-Resistant Clinics in Brazzaville, Republic of Congo - Gabriel, AHOMBO; Rachel, MOYEN; Tarcisse, BALOKI NGOULOU; Christian, KAYATH Aimé; Esther, ONTSIRA NGOYI Nina (International Journal of Innovative Research in Medical Science, 2019)
In order to demonstrate the transmission of resistance genes between clinical bacteria and community bacteria, 78 strains of Staphylococcus including 56 (71.79%) community strains and 22 (28.21%) clinical strains were isolated and identified according to classical methods of microbiology. The resistance pattern was determined by the standard Mueller Hinton diffusion method. The phenotype of methicillin-resistant Staphylococci was investigated from the oxacillin disc and cefoxitin. PCRs were performed on 45 DNA strains of Staphylococcus including 25 (55.56%) of community strains and 20 (44.44%) of clinical strains resistant to oxacillin and cefoxitin alone or associated. Phenotypic results indicate that norfloxacin, ciprofloxacin, tobramycin, kanamycine were more active on community Staphylococci. In clinical Staphylococcus, only tobramycin was more active. The differences were significant between the resistance frequencies of community and clinical Staphylococci for some antibiotics with a P value ˂0.05. The mec A gene was identified in 9 community S.aureus strains, 6 clinical strains of Staphylococcus. The fragments of the amplified gene were of the same molecular weight (500bp), which suggests a spread of clinical strains in the city.